6(x+3)=6x

Simple and best practice solution for 6(x+3)=6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+3)=6x equation:


Simplifying
6(x + 3) = 6x

Reorder the terms:
6(3 + x) = 6x
(3 * 6 + x * 6) = 6x
(18 + 6x) = 6x

Add '-6x' to each side of the equation.
18 + 6x + -6x = 6x + -6x

Combine like terms: 6x + -6x = 0
18 + 0 = 6x + -6x
18 = 6x + -6x

Combine like terms: 6x + -6x = 0
18 = 0

Solving
18 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| abs(2x^2-5)+6=7 | | 7y+3=6x+2 | | s^5+4s^4+4s^3=0 | | p*3.4=7.48 | | -138=-2+3(-6x+14) | | e^4x-e=0 | | 8y+4=9y | | x/8=5.6 | | 3x-5(3x-12)=156 | | 10×1/8= | | 10×1/8 | | 8sin(2x)-sin(4x)=0 | | ln(9x)+ln(4x)=5 | | 67.3=3.2q | | 188=4x+5(2x+4) | | y=3/2x-4/9 | | 4x-15x=66 | | 160=3x+7(4x-17) | | 3(3x+5)=36 | | 6x+2(6x-7)=76 | | 3a-2=5a | | (3x^2)+4=-5x+5 | | -10=6x+2(-x+13) | | 4m^2+17m+15=0 | | 32y^5+4y^3=0 | | (3x^2-4x)(2x^3+3x-1)=0 | | 2x-2(7x-2)=64 | | -(x-7)=5+2(x-1) | | 18m+5=13m+5 | | 1.08(1.21)(8-x)=10 | | x^2+4-9=0 | | 18c+7=6c-77 |

Equations solver categories